2002
DOI: 10.1046/j.1432-1327.2002.02820.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide regions involved in the activation of Escherichia coli outer membrane protease OmpT

Abstract: OmpT is an integral outer membrane protease of Escherichia coli. Overexpression of OmpT in E. coli and subsequent in vitro folding of the produced inclusion bodies yielded protein with a native-like structure. However, enzymatically active protease was only obtained after addition of the outer membrane lipid lipopolysaccharide (LPS). OmpT is the first example of an enzyme that requires LPS for activity. In this study, we investigated the nature of this activation. Circular dichroism analysis showed that bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 28 publications
12
89
0
2
Order By: Relevance
“…In this context, the decrease in the a-helical structures with decreasing water content (Table 1) may be understood. Our data are in rough accordance with those of Kramer et al (2002) who found no large structural changes of OmpT secondary structure on addition of LPS. This was surprising since the protease activity of OmpT was only obtained after addition of LPS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this context, the decrease in the a-helical structures with decreasing water content (Table 1) may be understood. Our data are in rough accordance with those of Kramer et al (2002) who found no large structural changes of OmpT secondary structure on addition of LPS. This was surprising since the protease activity of OmpT was only obtained after addition of LPS.…”
Section: Discussionsupporting
confidence: 93%
“…OmpT was recombinantly expressed in E. coli and purified from inclusion bodies as described previously (Kramer et al 2000(Kramer et al , 2002 with some modifications.…”
Section: Omptmentioning
confidence: 99%
“…1A, lane 3). Polymixin B is known to form a complex with the LPS, which are necessary for the activity of OmpT (32). The N-terminal sequence of the SC form, liberated by the purified LepB and OmpT together (Fig.…”
Section: In Vitro Cleavage Of Colicin D In Periplasmic Extracts-wementioning
confidence: 99%
“…Experimental evidence has been obtained recently showing that certain LPS structural motifs are recognized by outer membrane proteins (Omp) and that LPS plays a role for the correct folding and activity of proteins, such as PhoE (5), OmpT (6), and FhuA (7,8). The isolation and detailed structural characterization of all different glycoforms present in LPS from Escherichia coli J-5 aided the interpretation of results from in vitro folding experiments of outer membrane proteins (5,6) and furthermore gave an insight into the biosynthesis of LPS (9). Whereas the presence and distribution of negative charges is undoubtedly very important, the highly conserved nature of carbohydrates that build the inner core region implies that they are particularly suited to fulfill certain functions.…”
Section: Lipopolysaccharide (Lps)mentioning
confidence: 99%